1990
DOI: 10.1007/bf00180656
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic enzyme release and oxygen centered radical formation in human neutrophils are selectively inhibited by E-type prostaglandins but not by PGI2

Abstract: The action of PGE1, PGE2, PGI2 and iloprost on superoxide anion generation, lysosomal enzyme release, and changes of Ca2+ fluxes in human polymorphonuclear leukocytes (PMN) was studied in vitro. Both PGE-type compounds were equipotent inhibitors of FMLP-and PAF-stimulated superoxide anion generation, beta-glucuronidase release (IC50 3-5 mumol/l) and Ca2+ influx while PGI2 and iloprost were ineffective at concentrations up to 10 mumol/l. These inhibitory actions of PGE1 and PGE2 were paralleled by an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Gastric tissue levels of 6-keto-PGF 1␣ , a stable metabolite of PGI 2 , and PGE 2 were increased 30 min after WIR, which contributed to prevent the WIR-induced gastric mucosal injury mainly by inhibiting neutrophil activation (9,12,13,18). However, the mechanisms underlying the increase in the gastric tissue level of PGI 2 and PGE 2 have not been fully clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric tissue levels of 6-keto-PGF 1␣ , a stable metabolite of PGI 2 , and PGE 2 were increased 30 min after WIR, which contributed to prevent the WIR-induced gastric mucosal injury mainly by inhibiting neutrophil activation (9,12,13,18). However, the mechanisms underlying the increase in the gastric tissue level of PGI 2 and PGE 2 have not been fully clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Hecker et al (18) demonstrated that, although PGE 2 inhibited N-formyl-methionyl-leucyl-phenylalanine-induced cytotoxic enzyme release from human neutrophils by increasing intracellular levels of cAMP, neither PGI 2 nor iloprost, a stable analog of PGI 2 , had any effect. In contrast, Kainoh et al (22) reported that both PGE 2 and PGI 2 inhibited oxygen free radical production by increasing intracellular cAMP levels in rat polymorphonuclear leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism by which cyclic AMP inhibits O2-generation still remains to be elucidated. However, it has been demonstrated (Hecker et al, 1989;Ney & Schror, 1991) that the increase in intracellular cyclic AMP produced by PGE2 in human neutrophils is paralleled by a decrease in extracellular Ca2+ influx which may lead to the attenuation of receptor-mediated neutrophil activation by FMLP. It is interesting to note that Sedgwick et al (1985) found that although cyclic AMP levels increased in all neutrophils stimulated by the three different neutrophil activators, FMLP, phorbol myristate acetate and serum-treated zymosan, inhibition of 02-was seen only in the neutrophils treated with FMLP.…”
Section: Discussionmentioning
confidence: 99%
“…Human neutrophil activation is inhibited by prostaglandin E2 (PGE2) (Wong & Freund, 1980;Hecker et al, 1989) and PGD2 (Ney & Schror, 1991) and this has been linked to the ability of these compounds to activate adenylate cyclase. It has previously been shown that inhibition of N-formyl-methionylleucine-phenylalanine (FMLP)-induced superoxide generation by PGE2 is mediated by the occupation of EP2 receptors and activation of adenylate cyclase, leading to the elevation of intracellular levels of adenosine 3':5'-cyclic monophosphate (cyclic AMP) (Talpain et al, 1995).…”
Section: Introductionmentioning
confidence: 99%